An overview of Distributed Construction through Participatory Design - Zaphiris, Panayiotis; Laghos, Andrew; Zacharia, Giorgos (My University, 2005)
This article presents an empirical study of an online learning community that collaborates with the course design team under the Participatory Design methodology. The different phases of this methodology were implemented using a four-stage participatory design process (Zaphiris & Zacharia, 2001): 1) building bridges with the intended users, 2) mapping user needs and suggestions to the system, 3) developing a prototype, and 4) integrating feedback and continuing the iteration. We took advantage of the online and distributed nature of the student community to asynchronously design, implement, and study the course. We carried out the participatory design methodology by following the Distributed Constructionism pedagogical theory. During the different phases of the design process, we measured the student participation and the changes in their behavior when new design elements were introduced. We conclude that the most important element of this course was our discussion board, which helped us to promote student collaboration and the identification of the key community users who can participate productively in Participation Design activities. There are three main sections to this article. After defining the key terminology, our Participatory Design approach is presented and its linkage to the Distributed Constructionism pedagogical theory specified. The article ends with ideas for future research and a set of conclusions.